GAYA PENGELOLAAN KONFLIK DALAM KOMUNIKASI KELUARGA URBAN DI ERA DIGITAL - Ditha Prasanti; Putri Limilia (Universitas Lambung Mangkurat, 2018)
ABSTRACTAs social beings, humans learn to communicate in the smallest layer of society, the family. Without us knowing, in family relationships, humans experience various kinds of interactions that often also trigger the occurrence of conflict. This is what is interesting to study. Everyone in a family certainly has a conflict management style different from each other, especially for urban families. Moreover, the current digital era requires humans to use a variety of sophisticated digital media that continues to grow. Therefore, the researcher were interested to raise this research with the focus of study that is